Design and implementation of a remote virtual laboratory by internet applied to kuka lbr iiwa 14 r820 (2020)
In the educational field, it is necessary to have the ability to experiment for learning process, that is where virtual laboratories allow having more freedom to do it, even when there are no physical resources. In this paper is presented a web-based virtual laboratory with the KUKA LBR IIWA 14R820 robot. A virtual robotic arm was used in V-REP simulator allowing to control the robotic arm using the direct kinematic model, directly controlling the position of each joint or through the inverse kinematic model that was developed using Denavit-Hatenberg methodology. For connection with the remote API through the web and design of user interface, LabVIEW 2016 was used with some external libraries. For connection with laboratory through the web, the user had to have a computer with Internet access and have LabVIEW Run-Time Engine 2016 plugin installed. In experimental tests, it was observed that the system was robust since it allows streaming to several users without affecting the work of who is managing the program. It was possible to verify that the performance of the laboratory is linked to the working capacity of the user’s computer.